Proof: Do Expr At Unchanged 1
Let's prove the following theorem:
if the following are true:
- expression state at time 1 = "begin_expr"
- the expression at time 1 =
__eq__(1, 3)
then the expression at time 2 = __eq__(1, 3)
Proof:
Given
1 | expression state at time 1 = "begin_expr" |
---|---|
2 | the expression at time 1 = __eq__(1, 3) |
# | Claim | Reason |
---|---|---|
1 | the expression at time (1 + 1) = the expression at time 1 | if expression state at time 1 = "begin_expr", then the expression at time (1 + 1) = the expression at time 1 |
2 | the expression at time (1 + 1) = __eq__(1, 3) |
if the expression at time (1 + 1) = the expression at time 1 and the expression at time 1 = __eq__(1, 3) , then the expression at time (1 + 1) = __eq__(1, 3) |
3 | 1 + 1 = 2 | 1 + 1 = 2 |
4 | the expression at time (1 + 1) = the expression at time 2 | if 1 + 1 = 2, then the expression at time (1 + 1) = the expression at time 2 |
5 | the expression at time 2 = __eq__(1, 3) |
if the expression at time (1 + 1) = the expression at time 2 and the expression at time (1 + 1) = __eq__(1, 3) , then the expression at time 2 = __eq__(1, 3) |
Comments
Please log in to add comments